2022
DOI: 10.1101/2022.04.30.490133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tree diversity and density affect damage caused by the invasive pest Cameraria ohridella in urban areas

Abstract: Invasive, non-native invasive pests pose a growing threat to urban trees and the services they provide to urban residents. With the reluctance to use chemical insecticides in cities, environmentally friendly methods of pest management are needed. Tree diversity is known to affect insect herbivory in forest, with higher tree species diversity leading to lower level of damage. However, the validity of those findings for a non-native insect in an urban environment remains to be demonstrated.We monitored 54 horse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Paquette et al (2021) suggested that planting species from different functional groups improves functional diversity and thus increases urban forest resilience, because tree species with different traits will have different responses to threats. Urban forests face and will continue to face unexpected stressors associated with global change (e.g., climate change, novel pests or pathogens), such as the increasing frequency of drought events, the extension of urban heat islands, and the invasion of emerald ash borer, Dutch elm disease, and horse chestnut leafminer, which may lead to large losses of trees and their associated benefits (Raupp et al 2006;Ordóñez and Duinker 2015;Lovett et al 2016;Hudgins et al 2022;Stemmelen et al 2022). The particular problem encountered by city managers is the high uncertainty about what extreme weather events (e.g., wind storms, heat stress, ice), exotic insects, or diseases will hit next (Foran et al 2015), reinforcing the importance of increasing diversity to be better prepared for any eventuality.…”
Section: Comparison Of Existing Toolsmentioning
confidence: 99%
“…Paquette et al (2021) suggested that planting species from different functional groups improves functional diversity and thus increases urban forest resilience, because tree species with different traits will have different responses to threats. Urban forests face and will continue to face unexpected stressors associated with global change (e.g., climate change, novel pests or pathogens), such as the increasing frequency of drought events, the extension of urban heat islands, and the invasion of emerald ash borer, Dutch elm disease, and horse chestnut leafminer, which may lead to large losses of trees and their associated benefits (Raupp et al 2006;Ordóñez and Duinker 2015;Lovett et al 2016;Hudgins et al 2022;Stemmelen et al 2022). The particular problem encountered by city managers is the high uncertainty about what extreme weather events (e.g., wind storms, heat stress, ice), exotic insects, or diseases will hit next (Foran et al 2015), reinforcing the importance of increasing diversity to be better prepared for any eventuality.…”
Section: Comparison Of Existing Toolsmentioning
confidence: 99%